Trajectories after first‐episode psychosis: Complement to ambiguous outcomes of long‐term antipsychotic treatment by exploring a few hidden cases. Issue 4 (21st June 2018) - Liu, Chen‐Chung; Lin, Yi‐Ting; Liu, Chih‐Min; Hsieh, Ming H.; Chien, Yi‐Ling; Hwang, Tzung‐Jeng; Hwu, Hai‐Gwo
Abstract : Aim: Patient's long‐term phenomenology after first‐episode psychosis could be blurred due to early intervention. The contradictory messages regarding necessity of long‐term antipsychotic treatment derived from different methodologies warrants careful reappraisal. Methods: We approached a group of patients lost to follow‐up in a previous study. Targeting these 44 missing patients, we sent 2 carefully worded letters to invite them for interviews to see if their life trajectories were different from those who stayed in a university‐based hospital system. Results: A total of 21 patients replied, but only 8 agreed to in‐depth interviews. Of these, 2 warranted revision of their diagnoses as there had been no recurrence of psychotic symptoms and they had remained antipsychotic‐free for several years despite displaying a dysthymic state; 1 fulfilled remission criteria on intermittent low‐dose antipsychotics but kept a distance from any potential stressor; 1 achieved full remission with good functioning and discontinued medications for a year, but resumed taking antipsychotics after feeling an impending relapse; the other 4 showed common courses of chronic schizophrenia with repeated admission and/or rehabilitation programs in other service systems. Conclusions: The trajectories after first‐episode psychosis should not be over‐simplified by calculating the probability of relapse or the odds of achieving adequate functioning determined by medication adherence or not. Examining from a dynamic perspective employing a qualitative approach to take into account diagnostic stability, treatment preferences, psychosocial factors, individual coping strategies and personalized formulation of illness, we can gain more insight into the ambiguous information revealed by the recent literature.